2013
DOI: 10.1002/sia.5292
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube growth on high modulus carbon fibres: Morphological and interfacial characterization

Abstract: Carbon nanotubes (CNTs) were grown directly on the surface of carbon fibres, using the catalytic chemical vapour deposition. FeCo bimetallic catalysts were deposited on carbon fibres using a simple wet impregnation method. CNTs were synthesized over the prepared catalysts by the catalytic decomposition of acetylene at 750 o C. The uniform CNT formation on the fibre surface was verified using scanning electron microscopy. Raman spectroscopy was employed to evaluate non-destructively the CNT growth and the CNT q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The dominant peak (1595 cm −1 ) is assigned to the G band and the small feature at 1619 cm −1 is assigned to the D’ peak, which resides at 1620 cm −1 . This disorder peak was not observed for the 514 nm laser excitation energy, although it should be stated that the peak is sensitive to the area of the fibre and the chirality lattice orientation30. The lack of G − /G + splitting suggests the presence of MWCNTs, as corroborated the STEM measurements.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The dominant peak (1595 cm −1 ) is assigned to the G band and the small feature at 1619 cm −1 is assigned to the D’ peak, which resides at 1620 cm −1 . This disorder peak was not observed for the 514 nm laser excitation energy, although it should be stated that the peak is sensitive to the area of the fibre and the chirality lattice orientation30. The lack of G − /G + splitting suggests the presence of MWCNTs, as corroborated the STEM measurements.…”
Section: Resultssupporting
confidence: 70%
“…This interlayer also reduces the degradation to the underlying carbon fibre by the growth process20, acting as a thermal barrier21 and reducing catalyst-carbon fibre interaction, minmising pitting11. It is observed that the morphology of the CNTs exhibit similarities to those grown on alumina/SiC fibres222324, which further highlights that the improvements in the CNT growth result from the Al interlayer compared to current state of the art252627282930. SEM analysis of the dry fibres (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…carbon fibres. However, the level of enhancement is generally dependent on the degree of dispersion, impregnation, and interfacial adhesion of the CNTs in the polymer matrix [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…There are two approaches, using the overall CNT-g-CF diameter, which includes the cross-sectional area containing the CNTs [60] or only the diameter of the fiber substrate. [18,59,[65][66][67][68] There are no specific standards for either single fiber fragmentation tests nor single fiber pull-out tests, yet there is a large body of literature for traditional fiber-matrix systems. [69] Relative differences between a baseline sample and modified samples are typically preferred rather than absolute values due to large testing variability.…”
Section: Adhesion Properties Of (Cnt-g-)carbon Fibers To An Epoxy Matrixmentioning
confidence: 99%